Position of OLAF in a multi-level governance system of the European Union - Ruszkowski, Janusz (Przegla̦d europejski, 2019)
The author aims to investigate the position of OLAF in the multi-level governance system (MLG) ofthe European Union with specific inter-institutional consequences of such location, assuming thatOLAF is not a classical supranational institution. In the research subject an important role is playedby the European Commission (EC), which established OLAF and gave it specific competences to act.These facts are fundamentally important for further considerations, so they can have a major impacton the precise determination of OLAF’s position in the MLG. If OLAF as an agent and supervisorhas control powers over supranational institutions, including its principal, a supranational EuropeanCommission, it is unlikely that it would also be a supranational institution. This article demonstrates,that OLAF is not a classic supranational institution because it exhibits strong features of a supra--supranational institution operating in a multi-level EU governance system. A helpful theoretical andmethodological research tools we consider the Principal/Agent Theory (PAT) and its combinationPrincipal/Supervisor/Agent Theory (PSAT) on the one hand, and the concept of multi-level governance (MLG) on the other hand.